Pretransplant Immune- and Apoptosis-Related Gene Expression Is Associated with Kidney Allograft Function. (12th June 2016) - Kamińska, Dorota; Kościelska-Kasprzak, Katarzyna; Chudoba, Paweł; Mazanowska, Oktawia; Banasik, Mirosław; Żabinska, Marcelina; Boratyńska, Maria; Lepiesza, Agnieszka; Gomółkiewicz, Agnieszka; Dzięgiel, Piotr; Klinger, Marian
Abstract : Renal transplant candidates present immune dysregulation, caused by chronic uremia. The aim of the study was to investigate whether pretransplant peripheral blood gene expression of immune factors affects clinical outcome of renal allograft recipients. Methods . In a prospective study, we analyzed pretransplant peripheral blood gene expression in87 renal transplant candidates with real-time PCR on custom-designed low density arrays (TaqMan). Results . Immediate posttransplant graft function (14-day GFR) was influenced negatively by TGFB1 (P = 0.039 ) and positively by IL-2 gene expression (P = 0.040 ). Pretransplant blood mRNA expression of apoptosis-related genes ( CASP3, FAS, and IL-18 ) and Th1-derived cytokine gene IFNG correlated positively with short- (6-month GFR CASP3 :P = 0.027, FAS :P = 0.021, and IFNG :P = 0.029 ) and long-term graft function (24-month GFR CASP3 :P = 0.003, FAS :P = 0.033, IL-18 :P = 0.044, and IFNG: P = 0.04 ). Conclusion . Lowered pretransplant Th1-derived cytokine and apoptosis-related gene expressions were a hallmark of subsequent worse kidney function but not of acute rejection rate. The pretransplant IFNG and CASP3 and FAS and IL-18 genes' expression in the recipients' peripheral blood is the possible candidate for novel biomarker of short- and long-term allograft function.